2013
DOI: 10.1563/aaid-joi-d-11-00023
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Aspects of Human Mandibular Subperiosteal Dental Implants

Abstract: Clinical, microbiological, and biochemical features of human mandibular subperiosteal dental implants exhibiting peri-implantitis were compared with those experiencing long-term peri-implant health. After evaluation of clinical parameters, submucosal plaque samples were obtained from permucosal implant abutment posts exhibiting probing depths ≥5 mm and bleeding on probing in subjects with peri-implantitis (n = 3) and from posts with peri-implant health in subjects with long-term subperiosteal implant health (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…(), higher levels of GCF biomarkers in peri‐implantitis failed to be statistically significant due to a relatively small number of samples studied (Rams et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…(), higher levels of GCF biomarkers in peri‐implantitis failed to be statistically significant due to a relatively small number of samples studied (Rams et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, penicillin allergy per se cannot be considered as a risk factor for early failure so far. Instead, it seems more plausible that alternative antibiotics, such as in this case clindamycin, present a suboptimal efficacy [ 50 , 51 , 52 , 53 , 54 ] or a negative influence on osseointegration [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This drug may favor an increase in the proportions of resistant Prevotella species in saliva [37] and some, such as P. intermedia and P. aeruginosa, are often found in implants with peri-implantitis [38]. In this context, an in vitro study found that one or more pathogenic species found in implants with peri-implantitis, especially P. intermedia, Tannerella forsythia and Aggregatibacter actinomycetemcomitans, are resistant at therapeutic concentrations in 46.70% of cases to clindamycin [39]. In addition, several studies have linked the prescription of antibiotics other than beta-lactams to an increase in MRSA [33].…”
Section: Suboptimal Efficacy Of Alternative Antibiotics Such As Clindamycinmentioning
confidence: 99%